2019
DOI: 10.1177/1940082919872634
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Agenda for the Pantanal Wetland: Perspectives on a Collaborative Interface for Science, Policy, and Decision-Making

Abstract: Building bridges between environmental and political agendas is essential nowadays in face of the increasing human pressure on natural environments, including wetlands. Wetlands provide critical ecosystem services for humanity and can generate a considerable direct or indirect income to the local communities. To meet many of the sustainable development goals, we need to move our trajectory from the current environmental destructive development to a wiser wetland use. The current article contain a proposed agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
0
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 151 publications
(147 reference statements)
1
112
0
14
Order By: Relevance
“…These studies also demonstrated the temporal variation of those assemblages as a function of the dry and high-water periods, which are characteristic of this Pantanal region. This confirms their complexity and importance for the maintenance of the biodiversity of this floodplain (Junk et al 2006, Wantzen et al 2016, Tomas et al 2019.…”
Section: Introductionsupporting
confidence: 71%
“…These studies also demonstrated the temporal variation of those assemblages as a function of the dry and high-water periods, which are characteristic of this Pantanal region. This confirms their complexity and importance for the maintenance of the biodiversity of this floodplain (Junk et al 2006, Wantzen et al 2016, Tomas et al 2019.…”
Section: Introductionsupporting
confidence: 71%
“…Soil erosion has been increased by conversion of extensive areas to cropland (29% of the upland watershed area analyzed in this study) or pasture (22%) (Zeilhofer et al, 2006). Cattle ranching, subsistence and recreational fishing, and ecotourism are major economic activities within the Pantanal, and the floodplains are globally recognized by conservation organizations because they harbor important populations of several endangered mammals and birds (Tomás et al, 2019).…”
Section: Study Sitementioning
confidence: 98%
“…The reduction of ranching activities, and the abandonment of some ranches in the Pantanal and Patagonia, decreased conflict with jaguars and pumas and created refuges for predators and wild prey. Yet, ultimately, it was the synergy of livestock reductions, the creation of new protected areas in the Pantanal (Tomas et al, 2019) and Chilean Patagonia (Cuevas, 2015), and improving social tolerance for large carnivores that has made jaguar and puma tourism an increasingly important economic activity for both regions (Barrera et al, 2010; Sarno et al, 2019; Tortato et al, 2017). Additional contributing factors were the simultaneous surge in the global demand for wildlife tourism activities (Twining‐Ward, Li, Bhammar, & Wright, 2018) and the growing implementation of anti‐predation strategies for livestock in cattle ranches (e.g., Hoogesteijn et al, 2016).…”
Section: Discussionmentioning
confidence: 99%